Inserted hydrogen promotes oxidation catalysis of mixed Ru0.3Ti0.7O2 as exemplified with total propane oxidation and the HCl oxidation reaction. Issue 5 (19th January 2023) - Wang, Wei; Timmer, Phillip; Luciano, Alexander Spriewald; Wang, Yu; Weber, Tim; Glatthaar, Lorena; Guo, Yun; Smarsly, Bernd M.; Over, Herbert
Abstract : The solid solution of a reducible oxide with a (non or) less reducible oxide may open the way to incorporate substantial amounts of hydrogen by the simple exposure to H2 at elevated temperatures, as exemplified by the mixture of RuO2 and TiO2 . Abstract : The solid solution of a reducible oxide with a (non or) less reducible oxide may open the way to incorporate substantial amounts of hydrogen by the simple exposure to H2 at elevated temperatures, as exemplified with the mixture of RuO2 and TiO2 . We are able to incorporate 17.6 mol% hydrogen into the mixed oxide Ru0.3 Ti0.7 O2 by H2 exposure at 250 °C, while this is not possible for pure RuO2 and rutile TiO2 that is either reduced to metallic Ru or does not allow for hydrogen absorption, respectively. Hydrogenated Ru0.3 Ti0.7 O2 may be utilized in hydrogenation catalysis. In this study, however, we demonstrate that hydrogen-incorporated Ru0.3 Ti0.7 O2 improves substantially the catalytic performance in oxidation reactions such as the total oxidation of propane and HCl oxidation reaction. Hydrogen induced lattice strain in Ru0.3 Ti0.7 O2 accompanied with altered electronic properties is likely to be the reason for the observed enhancement in catalytic activity. Hydrogen treatment can also be performed in the reactor, thus providing an additional parameter to fine-tune in situ the catalytic performance of a mixed oxide catalyst.